2020
DOI: 10.48550/arxiv.2009.10707
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measuring Interstellar Delays of PSR J0613-0200 over 7 years, using the Large European Array for Pulsars

R. A. Main,
S. A. Sanidas,
J. Antoniadis
et al.

Abstract: Using data from the Large European Array for Pulsars (LEAP), and the Effelsberg telescope, we study the scintillation parameters of the millisecond pulsar PSR J0613−0200 over a 7 year timespan. The "secondary spectrum" -the 2D power spectrum of scintillationpresents the scattered power as a function of time delay, and contains the relative velocities of the pulsar, observer, and scattering material. We detect a persistent parabolic scintillation arc, suggesting scattering is dominated by a thin, anisotropic re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…if scattering and flux density variations caused by variable DM in scattering screens can be predicted. This will be especially the case in systems with solved scattering screen geometry, either through VLBI or multi-station time delays (Brisken et al 2010;Fadeev et al 2018;Simard et al 2019), or through annual variations of scintillation timescales and bandwidths (Rickett et al 2014;Reardon et al 2019) or scintillation arc curvatures (Reardon et al 2020;Main et al 2020).…”
Section: Conclusion and Further Workmentioning
confidence: 99%
“…if scattering and flux density variations caused by variable DM in scattering screens can be predicted. This will be especially the case in systems with solved scattering screen geometry, either through VLBI or multi-station time delays (Brisken et al 2010;Fadeev et al 2018;Simard et al 2019), or through annual variations of scintillation timescales and bandwidths (Rickett et al 2014;Reardon et al 2019) or scintillation arc curvatures (Reardon et al 2020;Main et al 2020).…”
Section: Conclusion and Further Workmentioning
confidence: 99%
“…In particular, for experiments designed to detect nanohertz GWs, advanced noise modeling techniques such as those discussed in Arzoumanian et al (2020b) will benefit greatly from disentangling the covariances between DM and scattering where precision down to ∼ 100s of nanoseconds is required (e.g., Lam et al 2018;Lam 2018;Lam et al 2019). Techniques such as cyclic spectroscopy (Dolch et al 2020;Turner et al 2020), or alternative methods of quantifying time-variable scattering such as those described in Main et al (2020) will be necessary to break this covariance.…”
Section: Implications For Precision Pulsar Timingmentioning
confidence: 99%
“…However this arc curvature model for PSR J0737−3039A was inferior to an earlier model of scintillation timescale variations observed in the dynamic spectrum (Ransom et al 2004), because the arcs were not sharp. Main et al (2020) has also observed annual arc curvature variations in the millisecond pulsar, PSR J0613−0200. PSR J0437−4715 was the first pulsar to have its full three-dimensional orbital motion determined (van Straten et al 2001), and it also has the most precisely measured distance of any pulsar, D = 156.79 ± 0.25 pc (Reardon et al 2016).…”
mentioning
confidence: 91%